Comparative literature : theory and practice - Deba, Amiẏa.; Das, Sisir Kumar (Shimla : Indian Institute of Advanced Study in association with Allied Publishers, New Delhi, 1989)
Papers presented at a seminar held at Indian Institute of Advanced Studies, Shimla on 22-26 June 1987.
Includes bibliographies.
Keywords: Comparative literature -- Congresses; Indic literature -- Congresses